Eonandeva gen. nov., a new distinctive genus from Eocene Baltic amber (Diptera: Chironomidae) - Zakrzewska, Marta; Giłka, Wojciech (Zootaxa, 2015)
A new fossil genus, Eonandeva gen. nov., with two new species: E. helva sp. nov. (type for the genus) and E. latistyla sp. nov., is described from Eocene Baltic amber (~45–40 Ma). Adult males of both new species show the wing venation pattern, shape and chaetotaxy typical for the tribe Tanytarsini. The characters defined as prior apomorphies for the new genus—the gonostylus with a subapical flattened lobe and the stout, strongly elongated superior volsella—separate Eonandeva from the closely related extant genus Nandeva Wiedenbrug, Reiss et Fittkau, 1998.